Mencerdaskan kehidupan bangsa pendidikan nasional menurut Undang-Undang Dasar NRI 1945 (Lembaga Pengkajian MPR RI, 2019)
Mencerdaskan kehidupan bangsa pendidikan nasional menurut Undang-Undang Dasar NRI 1945